Clinical evaluation of Kushmanda Ghrita in the management of depressive illness - Chandre, Rajni (Medknow Publications & Media Pvt Ltd, 2011)
Depressive illness has been considered as a problematic mental illness since antiquity. The treatment modalities of depressive illness are of many kinds. Use of Medhya Rasayana drugs is a unique method of treatment described in Ayurveda for depressive illness. Kushmanda (Benincasa hispida) is one of the Medhya Rasayana as described by Bhava Mishra. Ghrita is also considered as Medhya Rasayana by almost all Acharyas. Keeping this background Kushmanda Ghrita has been selected as a trial drug to treat the patients of depressive illness. The study was carried out in 35 clinically diagnosed cases of depressive illness by using DSM-IV diagnostic criteria of depressive illness. All patients were given 20 ml of Kushmanda Ghrita in two divided doses morning and evening with 40 ml of lukewarm water for a period of one month. It has shown statistically significant results with psychometric parameters–Hamilton depression rating scale (t = 24.36, P < 0.001), Hamilton anxiety rating scale (t = 26.20, P < .001), immediate memory span direct (t = 4.35, P < 0.001), and indirect test (t = 3.43, P < 01) along with clinical symptoms.